The interactive effect of grazing and fertilizer application on soil properties and bacterial community structures in a typical grassland in the central Inner Mongolia Plateau - Qi, Le; Zhang, Min; Yin, Jingjing; Ren, Weibo; Sun, Siyuan; Chen, Zhe; Yuan, Ting; Guo, Luyao (Frontiers in Ecology and Evolution, 2023)
Appropriate grazing intensity and fertilization of nitrogen (N) and phosphorus (P) are effective measures to increase grassland productivity. In order to study the effects of grazing intensity and fertilizer application on soil properties, enzyme characteristics, soil bacterial community compositions, 12 treatments (CC, CN, CP, CNP, LC, LN, LP, LNP, HC, HN, HP, HNP) with 3 grazing intensity levels: no grazing (C), light grazing (L) and heavy grazing (H), and 4 fertilizer application levels: no fertilizer addition (C), N fertilizer addition alone, P fertilizer addition alone, both N and P fertilizers addition (NP) were conducted in a typical grassland in Xilingol, Inner Mongolia. The results showed that grazing and fertilizer application increased the input of soil nutrients, and grazing significantly increased soil dissolved organic carbon (DOC), soil total nitrogen (TN) and available phosphorus (AP); Soil alkaline hydrolysis nitrogen and total carbon were higher in LN than in LC in 0-20 cm. Soil total phosphorus and AP were higher in LP than in LN and LNP in 0-10 cm. Soil catalase (CAT) activity was decreased by 29.4%, 23.5% and 26.5%, respectively, in LNP than in LC, LN and LP in 0-10 cm. Soil CAT activity was decreased in HN and HNP than in HP in 0-20 cm. The relative abundance of Actinobacteria was increased by 38.1% and 45.0% in HC than in CC and LC, respectively, in 0-10 cm, and was increased by 35.8% and 21.7% in LN and LNP, respectively, than in LC in 0-10 cm. The relative abundance of Proteobacteria was increased in LNP than in LC in 0-10 cm. Redundancy and correlation analysis further indicated that the variation of soil C, N and P induced by grazing and fertilizer application affected the soil enzyme and bacterial diversity in the grassland soil.